The Sociolinguistics of Ethiopian Sign Language : A Study of Language Use and Attitudes - Eyasu Hailu Tamene (Sociolinguistics in deaf communities series ;, 2017)
Ethiopian Sign Language (EthSL) emerged relatively recently; its development is closely tied to the establishment of the first school for deaf students in Addis Ababa by American missionaries in 1963. Today, EthSL is used by more than a million members of the Ethiopian Deaf community, but it remains an under-researched language. In this work, Eyasu Hailu Tamene presents a groundbreaking study of EthSL that touches on multiple aspects of Deaf people's lives in Ethiopia. Tamene collects data from three principal groups of people: deaf participants, teachers of deaf students, and parents of deaf children. He examines EthSL use within families, in formal and informal settings, and in various community spaces. He documents the awareness among different groups of the services available for deaf people, such as sign language interpreters and Deaf associations. He finds that members of the Deaf community show positive attitudes toward the use of EthSL and investigates the factors that impact those attitudes. His work indicates that there are still critical gaps in recognition and support for the use of EthSL, which can pose a threat to the vitality of the language. The Sociolinguistics of Ethiopian Sign Language will help to advance public understanding of EthSL and contribute to improved educational and social outcomes for the Deaf community in Ethiopia.